2013
DOI: 10.1016/j.jacc.2013.01.092
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography/Computed Tomography for Diagnosis of Prosthetic Valve Endocarditis

Abstract: The use of (18)F-FDG PET/CT was helpful for diagnosing PVE. The results of this study support the addition of abnormal FDG uptake as a novel major criterion for PVE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
95
0
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 448 publications
(108 citation statements)
references
References 30 publications
4
95
0
9
Order By: Relevance
“…The combination of MSCT with PET has been shown to have an added value over TTE/TEE in confirming PVE,65, 66 especially in patients with negative or doubtful echocardiographic results 67. On the basis of these data, the latest guidelines on the management of IE12 considered an abnormal activity around the site of the prosthetic valve detected on PET/MSCT as a “major criterion” of IE.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of MSCT with PET has been shown to have an added value over TTE/TEE in confirming PVE,65, 66 especially in patients with negative or doubtful echocardiographic results 67. On the basis of these data, the latest guidelines on the management of IE12 considered an abnormal activity around the site of the prosthetic valve detected on PET/MSCT as a “major criterion” of IE.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, other imaging techniques, such as multislice computed tomography (CT)8, 9, 10 and 18 F‐FDG ( 18 F‐fluorodeoxyglucose) positron emission tomography/CT10, 11, 12 have been shown to be useful particularly in the setting of suspected prosthetic valve IE11 and have been included in the new European Society of Cardiology (ESC) criteria 137 without significantly decreasing their specificity 11.…”
Section: Diagnosing Tavr Endocarditismentioning
confidence: 99%
“…18 F‐FDG positron emission tomography/CT has been shown to increase the sensitivity of the Duke criteria7 without significantly decreasing their specificity 11. However, positron emission tomography/CT has not been specifically studied in suspected TAVR‐IE, the value of cardiac CT is unknown in this setting, and the value of the combination of these techniques in a multimodality approach is unknown 6…”
Section: Diagnosing Tavr Endocarditismentioning
confidence: 99%
“…Despite the fact that PET with 18FDG has high sensitivity in the diagnosis of inflammation, a number of authors have noted a rather low specificity of the method [79,80,81]. In a study of Rouzet F. et al a comparison of PET-CT with 18FDG and SPECT-CT with 99 mTc-HMPAOlabeled autoleukocytes for diagnoses of endocarditis was performed, and it was shown that the scintigraphy study had a significantly higher diagnostic efficiency compared to PET [82 ].…”
mentioning
confidence: 99%